Estimates of genetic similarities and DNA fingerprinting of wheats (Tritium species) and triticale cultivars using molecular markers - GARG, MONIKA; SINGH, SUKHWINDER; SINGH, BALDEV; SINGH, KULDEEP; DHALIWAL, H S (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999-2000 to study the genetic similarities and DNA fingerprinting of bread wheat (Triticum aestivum L. emend. Fiori & Paol.), durum wheat (Triticum durum Desf.) and triticale cultivars using molccular markers). In this study 14 varieties of bread wheat, 1 of durum and 1 of triticale released for gencral cultivation since 1920, were analysed using amplified fragment length polymorphism (AFLP), random amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) markers. Since these varieties represent the spectrum of gcrmplasm present in breeders' working crossing blocks, the objective of this study was to establish the mugnitude of genetic diversity and to fingerprint the individual lines for intellectual property protcction. Total number of assay units were 31 random primers fot' RAPDs, 6 primer combinations for AFLPs and 25 primer pairs for SSR markers. Highest number of polymorphic bands per assay unit was observed for AFLPs (39.7), followed by RAPDs (12.7) and SSRs (4.0) but polymorphic information content (PIC) range was highest for SSRs (0.13-0.86). Based on estimation of genetic similarities, more realistic dendrogram was obtained from SSR compared to that obtained from AFLP or RAPD data. Most of the cultivars could be uniquely identified (fingerprinted) with SSR and RAPD markers but not with AFLPs.